2022
DOI: 10.3389/fendo.2022.1014558
|View full text |Cite
|
Sign up to set email alerts
|

GnRH-agonist pretreatment in hormone replacement therapy improves pregnancy outcomes in women with male-factor infertility

Abstract: ObjectiveThis study aimed to examine the efficacy of HRT with gonadotropin-releasing hormone agonist (GnRH-a) pre-treatment in women with male-factor infertility who underwent a frozen embryo transfer (FET) programme.DesignBetween January 2016 and October 2020, 2733 women with male-factor infertility who underwent the HRT protocol as the endometrial preparation method were enrolled at two Reproductive Medicine Centres. Patients were divided into two groups based on whether they had GnRH-a pre-treatment before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…And GnRH-a can improve pregnancy outcomes in patients with male-factor infertility in FET cycles. It may be that it can facilitate dialogue between embryo and endometrium ( Yu et al, 2022 ). It has been reported that pre-pregnancy BMI affects ART pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…And GnRH-a can improve pregnancy outcomes in patients with male-factor infertility in FET cycles. It may be that it can facilitate dialogue between embryo and endometrium ( Yu et al, 2022 ). It has been reported that pre-pregnancy BMI affects ART pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one prospective randomized trial uncovered that GnRHa-HRT was associated with significantly higher pregnancy (37.6% vs. 24%, odds ratio [OR] 1.8, 95% credible intervals [CI] 1.1-3.4), clinical pregnancy (24% vs. 11.3%, OR 2.5, 95% CI 1.2-5.5), and live birth (20% vs. 8.5%, OR 2.9, 95% CI 1.2-8) rates in patients with regular menstruation undergoing frozen-thawed cleavage-stage embryo transfer [23] . In addition, multiple retrospective studies have not achieved definitive conclusions [24][25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…The researchers who contributed to this Research Topic have published a total of 11 thematic articles, including 1 review, 2 meta-analyses, 7 original research articles, and 1 study protocol, which highlight optimal endometrial preparation protocols. Hormone replacement therapy (HRT) is currently the most widely used treatment due to its broad applicability and low cycle cancellation rate ( 3 ). Nevertheless, it is associated with an increased risk of complications during obstetrics and delivery ( 4 ).…”
Section: Obstetric and Perinatal Complicationsmentioning
confidence: 99%